Identification and Action Patterns of Two Chondroitin Sulfate Sulfatases From a Marine Bacterium Photobacterium sp. QA16 - Wei, Lin; Zhang, Qingdong; Lu, Danrong; Du, Min; Xu, Xiangyu; Wang, Wenshuang; Zhang, Yu-Zhong; Yuan, Xunyi; Li, Fuchuan (Frontiers in Microbiology, 2022)
Chondroitin sulfate (CS)/dermatan sulfate (DS) is a kind of sulfated polyanionic, linear polysaccharide belonging to glycosaminoglycan. CS/DS sulfatases, which specifically hydrolyze sulfate groups from CS/DS oligo-/polysaccharides, are potential tools for structural and functional studies of CD/DS. However, only a few sulfatases have been reported and characterized in detail to date. In this study, two CS/DS sulfatases, PB_3262 and PB_3285, were identified from the marine bacterium Photobacterium sp. QA16 and their action patterns were studied in detail. PB_3262 was characterized as a novel 4-O-endosulfatase that can effectively and specifically hydrolyze the 4-O-sulfate group of disaccharide GlcUAβ1–3GalNAc(4-O-sulfate) but not GlcUAβ1–3GalNAc(4,6-O-sulfate) and IdoUAα1–3GalNAc(4-O-sulfate) in CS/DS oligo-/polysaccharides, which is very different from the identified 4-O-endosulfatases in the substrate profile. In contrast, PB_3285 specifically hydrolyzes the 6-O-sulfate groups of GalNAc(6-O-sulfate) residues located at the reducing ends of the CS chains and is the first recombinantly expressed 6-O-exosulfatase to effectively act on CS oligosaccharides.